1,2(у-3)+0,8у= 2,3(у+4)-1,5у= 9,6(2+х)+0,4х= 3,8(х+5)-1,8х= 1,7(4+у)+1,3у=

vipdana228 vipdana228    2   02.07.2019 06:00    0

Ответы
Pomogiteπ Pomogiteπ  26.07.2020 13:49
1)1,2(у-3)+0,8у=1,2у-3,6+0,8у=2у-3,8
2)2,3(у+4)-1,5у=2,3у+9,2-1,5у=0,8у+9,2
3)9,6(2+х)+0,4х=19,2+9,6х+0,4х=19,2+10х
4)3,8(х+5)-1,8х=3,8х+19-1,8х=2х+19
5)1,7(4+у)+1,3у=6,8+1,7у+1,3у=6,8+3у
Я думаю, что так.Надеюсь, что з
ПОКАЗАТЬ ОТВЕТЫ
ls0xhand ls0xhand  26.07.2020 13:49
1.2(у-3)+0.8у=0
1.2у-3.6+0.8у=0
1.2у+0.8у=3.6
2у=3.6
у=1.8
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика